Sleep Quality of Patient Hypertension with Obstructive Sleep Apnea (OSA) in the Elderly - Shobihatus Syifak; Dyah Yuniati; Nurlisa Naila Aulia; Iis Noventi (LPPM Universitas Harapan Bangsa, 2026)
Background: Hypertension is a common chronic health problem in older adult and is often associated with sleep disorders, one of which is the risk of Obstructive Sleep Apnoea (OSA). OSA can cause sleep fragmentation and intermittent hypoxia, which can lead to a decline with hypertension, sleep disorders often go undetected early on requiring effective screening efforts. Purpose: This study aims to analyze the relationship between sleep quality and the risk of Obstructive Sleep Apnoea (OSA) in elderly people with hypertension. Methods: This study employed an analytical observational design with a cross-sectional approach. This study was conducted at the Neurology Clinic of RSI Jemursari Surabaya from May to August 2025 with a sample size of 30 elderly individuals selected using simple random sampling. Sleep quality was measured using the Pittsburgh Slee Quality Index (PSQI), while the risk of OSA was assessed using the Epworth Sleepiness Scale (ESS). The relationship between sleep quality and the risk of OSA was analysed usinhg Fisher’s exact test with a significance level of 0.05. Result: The result showed that most elderly people with hypertension had poor sleep quality (PSQI > 5). Elderly people with a poor sleep quality were significantly more likely to have an ESS score ≥10, indicating an increased risk of Obstructive Sleep Apnoea, compared to elderly people with good sleep quality (p = 0.021). Conclusion: There is a significant relationship between sleep quality and the risk of Obstructive Sleep Apnoea in elderly people with hypertension. Screening for sleep quality and OSA risk using the PSQI and ESS is important as an early detection measure to support the prevention of cardiovascular complications improve the quality of life of elderly people.